MODEL PEMBERDAYAAN PEREMPUAN MELALUI PROGRAM KOPERASI DIGITAL DI WILAYAH PERKOTAAN - Melyana R Pugu; Andjani Trimawarni; Sangrila Puspita Dewi; Al-Amin (BORJUIS: JURNAL OF ECONOMY, 2025)
The purpose of this research is to analyze the Model of Women's Empowerment Through Digital Cooperative Programs in Urban Areas. The method of this research is the form of this research is descriptive, analytical, and critical. Therefore, the author can comprehensively describe how the Women's Empowerment Model through Digital Cooperative Programs in Urban Areas is modeled. In this study, the author optimally uses two data sources related to this research, namely. Primary data sources and secondary data sources. The main sources of this research are books and scientific journals on the Women's Empowerment Model. The results of this study are that the model of women's empowerment through digital cooperatives in urban areas has proven to be effective in increasing women's economic independence and digital literacy. However, challenges such as technology access, social support, and product innovation need to be addressed to ensure the sustainability and long-term positive impact of these programs.